Super polluters : tackling the world's largest sites of climate-disrupting emissions - Grant, Don S.; Jorgenson, Andrew; Longhofer, Wesley (Society and the environment., 2020)
"Power plants are the lifeblood and bane of modern society. Electrification has revolutionized transportation and communication, dramatically improved medical care, spurred the rise of the metropolis, and enabled the global population to grow by over four billion during the past century. But because fossil fueled power plants are the largest source of human caused greenhouse gases, they also pose the single greatest threat to humans' life support system. Despite their pivotal role in society and projections that electricity generation will increase by 60% over the next two decades, however, there is little analysis of the causes and possible abatement of power plants' carbon pollution. Fortunately, as more scientists address the intersection of societies and their environments, especially in the context of climate change, they raise important questions about the distribution of pollution within sectors like electricity and have identified factors that may explain why certain actors within them do more environmental harm than others. These factors include technology, size, and age, but also their nation's position in the world economy, embeddedness in global environmental norms, political-legal systems, and the policies of their local governments. With Super Polluters, Don Grant, Andrew Jorgenson, and Wesley Longhofer present a novel data set on the CO2 emissions and structural attributes of nearly 20,000 fossil fuel power plants in 148 countries and information from the Environmental Protection Agency's Greenhouse Gas Reporting Program. They illustrate how social scientists can advance our understanding of the determinants and mitigation of individual power plants' carbon pollution"--